Detection of the Early Cardiac changes of hypertension by Echocardiography - Hussein, Muataz F.; Wahbi Al-Kadi, Ramaq G.; Zaki, Anmar S. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: Hypertension causes changes on the cardiac performance, and this effect is more profound on the LV where systolic high pressure is present. Patients and Methods: We studied 30 patients (14 females and 16 males of average age of 54.8±13.5) with hypertension and 20 normal individuals, the control group (age range 45.6±17.8, 11 females and 9 males). Measurements of early filling velocity E, late filling velocity A at atrial contraction and ejection fraction were taken, also isovolumetric relaxation, and contraction times and ejection times were taken. MPI myocardial performance index was calculated. Results: Results shows a significant increase in the isovolumetric relaxation time IRT (30%),were IRT for the patients group was(105.4±20.8)compared to(73±6.86) for the normal group. The late velocity A (42%), were A for the patients group was (89.28±18) compared to (51.1±18) for the normal group. Ejection time ET (26%), were ET (438.2±88) for the patients group compared to (324±34) for the normal group. And the ratio A/E (41%), were A/E for patients group (1.33) compared to (0.78) for the normal group. While no significant change was observed on ejection fraction (EF %), isovolumetric contraction time (ICT), early velocity E, and myocardial performance index (MPI). Conclusion: Diastolic function impairment was found to occur earlier than systolic function impairment in hypertensive patients.